2021
DOI: 10.3389/fmicb.2021.593023
|View full text |Cite
|
Sign up to set email alerts
|

Rhizodegradation of Pyrene by a Non-pathogenic Klebsiella pneumoniae Isolate Applied With Tagetes erecta L. and Changes in the Rhizobacterial Community

Abstract: The non-clinical Klebsiella pneumoniae variants, isolated from different environments, are now well acknowledged for their role in plant-growth promotion and biodegradation of pollutants. In the present study, a non-clinical environmental isolate K. pneumoniae AWD5 is being described for rhizoremediation of pyrene, applied through the rhizosphere of an ornamental plant, Tagetes erecta L (marigold). The non-pathogenic nature of AWD5 was established using an in vivo mouse model experiment, where AWD5 was unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Moreover, P. aeruginosa NCIM 5514 degraded 61.0% of crude oil during 60 days of incubation (Varjani and Upasani 2016). Rajkumari et al (2021) reported that a non-clinical environmental isolate K. pneumoniae AWD5 was achieved 87.5% of pyrene degradation in the presence of succinate as Fig. 1 The petroleum degradation and bacterial growth of Kp1, Kp2 and Kp RSKK 574 strains co-substrate within 21 days of incubation (Rajkumari et al 2021).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, P. aeruginosa NCIM 5514 degraded 61.0% of crude oil during 60 days of incubation (Varjani and Upasani 2016). Rajkumari et al (2021) reported that a non-clinical environmental isolate K. pneumoniae AWD5 was achieved 87.5% of pyrene degradation in the presence of succinate as Fig. 1 The petroleum degradation and bacterial growth of Kp1, Kp2 and Kp RSKK 574 strains co-substrate within 21 days of incubation (Rajkumari et al 2021).…”
Section: Resultsmentioning
confidence: 98%
“…Rajkumari et al (2021) reported that a non-clinical environmental isolate K. pneumoniae AWD5 was achieved 87.5% of pyrene degradation in the presence of succinate as Fig. 1 The petroleum degradation and bacterial growth of Kp1, Kp2 and Kp RSKK 574 strains co-substrate within 21 days of incubation (Rajkumari et al 2021). It is known that various microorganisms can metabolize different groups of hydrocarbons as straight, branched, and cyclic alkanes and aromatics as a sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…However, 49 clinical strains were also not detected with these two major virulent genes (Figure 6). Rhizosphere soil AWD5 K. pneumoniae is avirulent in the lung infection mice model (Rajkumari et al, 2021). The AMR and virulence characteristics are overlapped in both clinical and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that marigold flowers have antibacterial effects (Cahyaningrum et al, 2020), antimicrobial (Padalia and Chand, 2015), antimalarial , antihyperlipidemic (Kresnapati et al, 2021), and anti-inflammatory (Selvam et al, 2021). Flavonoid compounds have maximum inhibitory activity of K. pneumonia (Rajkumari et al, 2021). Marigold flower essential oil has antifungal activity and the maximum apoptotic rate of 90%, as seen from the HepG2 cell line at 82 and 122 g/ml (Safar et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The androgen dihydrotestosterone hormone causes excess oil production in the skin. This hormone can increase the size of the sebaceous glands, which has implications for sebum production in the skin (Cahyaningrum et al, 2020;Rajkumari et al, 2021). This situation makes it easier for acne causing bacteria to grow ideally (Puluh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%